Manufacturing of inorganic-organic hybrid solar cells by screen printing method - Hameş, Yakup; San, Sait Eren; Özdal, Teoman; Aslan, Erdem; Çabalak, Hasip; Şar, Hüseyin (My University, 2010)
In this study, hybrid bulk heterojunction (BHJ) organic solar cells with a poly(3-hexylthiophene-2,5- diyl)(P3HT):(6,6)-phenyl C61 -butyric acid methyl ester (PC61BM) active layer, a poly(3,4-ethylenedioxythiophene)- poly(styrenesulfonate)(PEDOT:PSS) buffer layer, and an electrochemically deposited zinc oxide (ZnO) n-type inorganic layer were produced. The PET/ITO/ZnO/PEDOT:PSS/P3HT:PC61 BM/Al device was manufactured and tested under solar illumination (AM1.5G, 100 mW/cm2). © TÜBİTAK. © 2011 Elsevier B.V., All rights reserved.
Keywords: P3HT/PCBM blends; Photovoltaic; Polymer solar cells; Screen printing; ZnO